The Macroeconomic Impact of Export-Oriented Facilities for Small and Medium Enterprises (SMEs) in Bali: Dampak Secara Makro Ekonomi Pemberian Fasilitas KITE Bagi Industri Kecil dan Menengah di Bali - Usman Fadli; Luh Putu Mahyuni (Green Publisher Indonesia, 2025)
The MSMEs sector plays a vital role in economic development of small island like Bali, significantly contributes to Regional Original Income (PAD), and provides employment opportunities across various sectors. With Bali’s rural and natural richness, MSME sector of handicrafts and tourism-related products, has great growth potential, both domestic and global markets. Denpasar Customs is here to support the economic growth of MSMEs by providing KITE IKM facilities. The main objective of the KITE IKM facilities are to provide easy procedures and fiscal incentives to trigger increased production of export goods and business expansion to global markets. This study examined the impact of the KITE IKM facilities by MSMEs in Bali especially in its influence on export value, investment value and labor absorption. With such a huge profit potential, there are still a small number of SMEs who have never used it and there are also SMEs who have stopped using the facilities. The study found both internal and external problems included not sharing enough knowledge, governance struggle, and stakeholders not working together. The findings highlighted the need for improved communication, education, and policy adjustments to enhance MSMEs participation in export activities, ensuring the maximization of fiscal incentives. By addressing these barriers, this study aimed to provide insights into policy formulation that will support sustainable MSME growth, stimulate exports, and promote economic empowerment in Bali. The research aims to contribute to enhancing the efficiency of government policies and supporting MSMEs in achieving their maximum economic potential.